THE INFLUENCE OF MATERNAL KNOWLEDGE, ATTITUDES AND PARENTING PRACTICES ON THE INCIDENCE OF STUNTING IN THE CAPITAL CITY OF CENTRAL LAMPUNG REGENCY, INDONESIA - Zuraida, Reni; Angraini, Dian Isti; Yunianto, Andi Eka; Nurtandhee, Mutiara (Universitas Airlangga, 2025)
The World Health Organization (WHO, 2021) classifies stunting as a major global health issue with a prevalence of 22% or around 149.2 million children in 2020. Factors such as maternal knowledge about nutrition, maternal attitudes towards meeting children's nutritional needs, and parenting practices are important in determining children's nutritional status and the risk of stunting, which can hurt adulthood. This study aims to examine the impact of maternal knowledge, attitudes, and childcare practices on the incidence of stunting in Central Lampung Regency. This study used a cross-sectional survey design involving 360 children aged 0–59 months selected by purposive sampling from six sub-districts. The data collected included child characteristics, nutritional status, maternal nutritional knowledge, attitudes, and practices using a validated questionnaire from previous studies. The LAZ/HAZ, WLZ/WHZ, and WAZ indicators measured children's nutritional status. Data analysis was done using the Partial Least Square Structural Equation Modelling (PLS-SEM) method with SmartPLS 3.0. The results showed maternal knowledge significantly affected attitudes (p = 0.001 for Attitude1; p = 0.026 for Attitude2) but not parenting practices (p = 0.986). Maternal parenting practices had a significant effect on children's meal frequency (p = 0.000) but not on the incidence of malnutrition (p = 0.259) and stunting (p = 0.174). These findings emphasize the importance of interventions that improve maternal knowledge and parenting practices to reduce the risk of stunting.